Provider Education about Glaucoma and Glaucoma Medications during Videotaped Medical Visits. (24th April 2014) - Sleath, Betsy; Blalock, Susan J.; Carpenter, Delesha M.; Muir, Kelly W.; Sayner, Robyn; Lawrence, Scott; Giangiacomo, Annette L.; Hartnett, Mary Elizabeth; Tudor, Gail; Goldsmith, Jason; Robin, Alan L.
Abstract : Objective . The purpose of this study was to examine how patient, physician, and situational factors are associated with the extent to which providers educate patients about glaucoma and glaucoma medications, and which patient and provider characteristics are associated with whether providers educate patients about glaucoma and glaucoma medications. Methods . Patients with glaucoma who were newly prescribed or on glaucoma medications were recruited and a cross-sectional study was conducted at six ophthalmology clinics. Patients' visits were videotape recorded and patients were interviewed after visits. Generalized estimating equations were used to analyze the data. Results . Two hundred and seventy-nine patients participated. Providers were significantly more likely to educate patients about glaucoma and glaucoma medications if they were newly prescribed glaucoma medications. Providers were significantly less likely to educate African American patients about glaucoma. Providers were significantly less likely to educate patients of lower health literacy about glaucoma medications. Conclusion . Eye care providers did not always educate patients about glaucoma or glaucoma medications. Practice Implications . Providers should consider educating more patients about what glaucoma is and how it is treated so that glaucoma patients can better understand their disease. Even if a patient has already been educated once, it is important to reinforce what has been taught before.